Efeitos do óleo essencial de Origanum Vulgare L. sobre o crescimento de bactérias patogênicas e tecnológicas em queijo de coalho - Souza, Geany Targino de (2016)
Coalho cheese is a semi-hard cheese typically produced in the Northeast region of Brazil using an enzymatic coagulating agent and mesophilic lactic acid starter cultures. Some physicochemical characteristics of this product, such as low acidity, high moisture and pH, may favor the survival and growth de pathogenic bacteria frequently associated to food outbreaks. Increasing concerns about the safety of cheeses, have led to the development of alternative preservation techniques using naturally derived ingredients as essential oils (EOs) to ensure the microbiological quality of these products. EO from Origanum vulgare L. (oregano – OVEO) has recognized inhibitory effects against pathogenic bacteria associated to cheeses, however, there is a lack of information regarding the effects of OVEO toward lactic acid bacteria used as starter cultures in processing of these products. Considering these aspects, with the present study aimed to evaluate the effects of OVEO on the cell viabilities of strains Staphylococcus aureus and Listeria monocytogenes, well as of strains Lactococcus spp. used in the processing of coalho cheese. These effects were measured by determination of minimum inhibitory concentration (MIC) of OVEO in microdilution in broth and assessing the viability of pathogenic and starter strains in cheese based broth containing OVEO (0.60 μL.mL-1, 1.25 μL.mL-1, 2.5 μL.mL-1 e 5 μL.mL-1) at 37 °C, 24 h and in semi-solid coalho cheese (0.60 μL.g-1, 1.25 μL.g-1 e 2.5 μL.g-1) at 10 °C during 72 h. The major constituents of OVEO, identified by gas chromatography coupled to mass spectrometry GC-MS were carvacrol (69,0%) and thymol (14.12%). MIC of OVEO was 2.5 μL.mL-1 against both S. aureus and L. monocytogenes and 0.6 μL.mL-1 against the tested starter co-culture. Assays in cheese-based broth containing OVEO at 0.6 μL.mL-1 revealed no decrease in viable cell counts of both pathogenic bacteria, while the starter co-culture decreased 1.0 CFU.mL-1 after 24 h of exposure compared with the initial viable counts. OVEO at 1.25 μL.mL-1 and 2.5 μL.mL-1 caused reductions of up to 2.0 log CFU.mL-1 and 2.5 log CFU.mL-1 in S. aureus and L. monocytogenes, respectively. At these same concentrations, OVEO severely affected the cell viability of the starter co-culture following a short period of exposure. Higher concentrations of OVEO were required to decrease the viable cell counts of all target bacteria in the semi-solid coalho cheese model compared to cheese-based broth. Over the assessed time points, viable cell counts of Lactococcus spp. in coalho cheese containing OVEO were lower than those of S. aureus and L. monocytogenes. These results suggest that the concentrations of OVEO used to control pathogenic bacteria in semi-hard cheese could be carefully evaluated because of their possible inhibitory effects on the growth and survival of starter lactic acid culture used during the production of this product.